Uncovering Students' Problem-Solving Gaps in Basic Chemistry Through Rasch Analysis - Sri Rejeki Dwi Astuti; Pramudya Dwi Aristya Putra; Nur Ahmad; Firdha Yusmar; Jadnika Dwi Rakhmawan Amrullah; Ika Nur Fitriani (Yayasan Keluarga Guru Mandiri, 2026)
Problem-solving skills are fundamental competencies in science education, particularly in basic chemistry, as they enable students to implement conceptual knowledge to real-life phenomena. This study aims to examine the psychometric properties of the problem-based chemistry test and to describe students' problem-solving skills. The test consisted of five essay-based problem-solving items administered to 123 first-year biology education students enrolled in a general chemistry course. Data were analyzed using EFA with SPSS 25 and Rasch Model with Winsteps Software version 3.73. The results indicated that all items fit the Rasch Model and demonstrated good item reliability, with a range of difficulty levels. However, person reliability was low, suggesting that the test had limited sensitivity in differentiating students' ability levels. Analysis of students' abilities revealed that most students were classified as having low to very low problem-solving skills, while a smaller proportion demonstrated moderate to high ability. A substantial number of persons misfit were identified, indicating irregular response patterns that may be influenced by test-taking behavior or the open-ended nature of the items. These findings suggest that the test is suitable for formative and diagnostic assessment of problem-solving skills in basic chemistry; however, further refinement and additional items are suggested to improve measurement precision.